Spaying cull cows and tt's effect on the weight gain of the cow and calf - Restle, João; Grassi, Celso (Pesquisa Agropecuaria Brasileira, 1993)
Weight gain, during suckling and finishing periods, of spayed beef cows was evaluated. Cows were spayed approximately 60 days after calving. Cows and calves were kept on pasture. Average daily gain, during suckling period, was 276 and 280 g (P >. 9102), respectively, for spayed and nonspayed cows. After weaning, during the 147 days finishing period, no significant difference was observed between the average daily gain of the two groups of cows (536 and 586 g; P >. 4129). Calves raised by spayed cows had similar (P >. 09) average daily gain (646 g) to those raised by nonspayed cows (682 g).
Keywords: beef cattle; suckling; finishing period